2002
DOI: 10.3102/01623737024002081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Professional Development on Teachers’ Instruction: Results from a Three-year Longitudinal Study

Abstract: This article examines the effects of professional development on teachers’ instruction. Using a purposefully selected sample of about 207 teachers in 30 schools, in 10 districts in five states, we examine features of teachers’ professional development and its effects on changing teaching practice in mathematics and science from 1996–1999. We found that professional development focused on specific instructional practices increases teachers’ use of those practices in the classroom. Furthermore, we found that spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
773
3
43

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,050 publications
(889 citation statements)
references
References 18 publications
(19 reference statements)
20
773
3
43
Order By: Relevance
“…By contrast, teachers who participated in professional development focused on instructional strategies not linked to specific content or who had limited exposure to professional development changed their practice very little. A number of subsequent studies, including nationally representative surveys of teachers and experimental evaluations of professional development, have found evidence of a link between content-focused professional development of an extended duration and changes to teachers' practice (e.g., Desimone et al 2002;Penuel and Gallagher 2009).…”
Section: Teacher Learning In Organized Professional Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, teachers who participated in professional development focused on instructional strategies not linked to specific content or who had limited exposure to professional development changed their practice very little. A number of subsequent studies, including nationally representative surveys of teachers and experimental evaluations of professional development, have found evidence of a link between content-focused professional development of an extended duration and changes to teachers' practice (e.g., Desimone et al 2002;Penuel and Gallagher 2009).…”
Section: Teacher Learning In Organized Professional Developmentmentioning
confidence: 99%
“…practice when it is sustained over time, focuses on enhancing the knowledge and skill needed to teach in specific content areas, employs active learning strategies in which teachers practice new pedagogical skills and receive feedback from others, and creates opportunities for collaborative learning from peers (Desimone et al 2002). Professional development with these characteristics can also support better curriculum implementation (Penuel et al 2007) and enhanced student learning Saxe et al 2001).…”
mentioning
confidence: 99%
“…Researchers note the importance of PD in ensuring that teachers develop the appropriate skills, knowledge, and instructional strategies needed to help students achieve meaningful science experiences (Desimone et al 2002;Hewson 2007;Opfer and Pedder 2011). Capps et al (2012) confirmed the importance of designing inquiry-based science PD to support science teachers' enactment of classroom inquiry.…”
Section: Professional Developmentmentioning
confidence: 99%
“…For instance, regarding the issue of cram schools, Euna was very concerned about the interruptions made by students who attended cram schools but did not come up with specific solutions, whereas Miyeong identified the issue of cram schools as "bad habits in learning mathematics." This indicates that cooperation with colleagues, particularly with more experienced teachers, is important in developing mathematics teachers' expertise, as previous research has evidenced (Garet et al 2001;Desimone et al 2002).…”
Section: Complexities Perceived By the Two Teachersmentioning
confidence: 72%